ANALYSIS OF THE INFLUENCE OF SYSTEM QUALITY, INFORMATION QUALITY AND SERVICE QUALITY ON ANCOL APP USER SATISFACTION - Sofiani Sofiani (International Journal Of Tourism, 2023)
The development of communication and information technology has been utilized by various sectors in the world including tourism. Technological advances are used to market and sell products from tourist destinations. However, Ancol App as a platform to marker dan sell tickets as as product from Ancol itself received a fairly low rating on both the App Store and Google PlayStore, this shows that there is a need for improvements to the quality of the system, the quality of information, and the quality of services provided to users.  This study is intended to know how the influence of system quality, information quality, and service quality on user satisfaction from Ancol App. Research methods were carried out with quantitative descriptive with a sample of 100 people who successfully made transactions using Ancol App. Sample collection techniques using Non-Probability Sampling type purposive sampling.  The results showed that (1) System Quality (X1) and Information Quality (X2) partially had no effect, while Service Quality (X3) had a positive effect on User Satisfaction (Y). (2) Simultaneously, System Quality (X1), Information Quality (X2), and Service Quality (X3) have a positive effect on User Satisfaction (Y). Based on the results of the descriptive analysis of the research, it is hoped that Ancol App can improve the quality of information and services in order to increase user satisfaction.